1993
DOI: 10.1901/jaba.1993.26-23
|View full text |Cite
|
Sign up to set email alerts
|

Functional Communication Training With and Without Extinction and Punishment

Abstract: Functional communication training has been reported to be a promising treatment for severe behavior problems. In this study, functional communication training alone and combined with extinction and/or punishment was evaluated for 4 clients with severe retardation, behavior problems, and communication deficits. The participants were inpatients on a hospital unit for treatment of severe behavior disorders. They received individualized interventions based on functional assessment that included reinforcement of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
243
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(251 citation statements)
references
References 16 publications
7
243
1
Order By: Relevance
“…For some children, FCT results in an acceptable reduction in problem behavior only when a punishment procedure is added to the treatment (Fisher et al, 1993;Wacker et al, 1990). This was also the case in a study by Hanley, Piazza, Fisher, and Maglieri (2005), who showed that FCT was ineffective for two children with intellectual disabilities and autism, whereas FCT plus punishment (e.g., a 30-s hands-down procedure) was effective in reducing severe self-injury, aggression, and disruption.…”
Section: Single-person Applicationsmentioning
confidence: 76%
“…For some children, FCT results in an acceptable reduction in problem behavior only when a punishment procedure is added to the treatment (Fisher et al, 1993;Wacker et al, 1990). This was also the case in a study by Hanley, Piazza, Fisher, and Maglieri (2005), who showed that FCT was ineffective for two children with intellectual disabilities and autism, whereas FCT plus punishment (e.g., a 30-s hands-down procedure) was effective in reducing severe self-injury, aggression, and disruption.…”
Section: Single-person Applicationsmentioning
confidence: 76%
“…Although the use of concurrent-operants arrangements has proven useful in the identification of specific dimensions of reinforcement that increase specific behaviors, treatment programs may initially require reductive procedures (e.g., extinction or punishment) to reduce inappropriate behaviors to acceptable levels (Fisher et al, 1993;Wacker et al, 1990). Previous investigations have evaluated the efficacy of extinction procedures in the reduction of aberrant behavior (Lerman & Iwata, 1996).…”
mentioning
confidence: 99%
“…Many procedural variations of the tangi- ble condition have been described in the literature (e.g., Fisher et al, 1993;Mueller et al, 2001). Future research on procedural aspects of this condition would be instructive.…”
Section: Resultsmentioning
confidence: 91%